Case Study : Corner Kick Café / Muhammad Hisyam Ismail - Ismail, Muhammad Hisyam (2020)
This case study is provided to the student since the project enable student to know more about a company situation and enable them to think out of a solution to handle them. As a UiTM student that learn ENT600, every student must take part in this case study. For this project, I interviewed Corner Kick Café in Sungai Besar, Selangor. One of the objectives for the project is to study on the background of the company, how the company works, and the products and services provided by Corner Kick Cafe. Other than that, look on how the cafe handle their services, to identify the problems occurs especially on food provision as Corner Kick Café selling food and beverage. Next, we also interviewed the manager on how they promote their business. Lastly, I also obtained some information on their financial achievements. In this case study, we discussed on the problems faced by the company. In order to analyze the company more, I listed the strength, weakness, opportunities and threats of the company by using SWOT analysis. Thus, I invented an innovation to improve the technology used in fillet fish.